The guilty dead: a monkeewrench novel - Tracy, P. J. (Tracy, P. J. Monkeewrench novel., 2018)
Gregory Norwood is Minnesota's most beloved philanthropist, and the story of his son's overdose was splashed across the front page of all the papers. When a photojournalist sets out to get a candid shot of the highly successful businessman on the one year anniversary of his son's death, he's shocked to find Norwood dead with a smoking gun in his hand. The city is devastated, and Minneapolis detectives Leo Magozzi and Gino Rolseth are called in to handle the delicate case. It should be open and shut, but something is not right. Norwood's death is no suicide. With no suspects and an increasing tangle of digital evidence that confounds the Minneapolis Police Department's most seasoned cops, Magozzi calls on Grace MacBride, Monkeewrench Software's founder and chief computer genius and the soon to be mother of their child together. She and her motley crew of partners begin to unravel connections between Norwood's death and an even larger plot. Norwood wasn't the first, won't be the last, and by the end, may be just one of many to die.